2016
DOI: 10.2807/1560-7917.es.2016.21.37.30338
|View full text |Cite
|
Sign up to set email alerts
|

Towards a consensus on genotyping schemes for surveillance and outbreak investigations of Cryptosporidium, Berlin, June 2016

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
(9 reference statements)
3
21
0
Order By: Relevance
“…However, to date, no sufficiently discriminatory multilocus genotyping scheme has been fully validated or widely adopted by veterinary or public health researchers (Hotchkiss et al., ) or reference laboratories in Europe, although an initiative as part of COST Action Euro‐FBP is addressing this issue (Chalmers and Cacciò, ). However, in most countries Cryptosporidium is not routinely genotyped, or even the infecting or contaminating species identified, and so point of reservoir source attribution is further hampered.…”
Section: Assessmentmentioning
confidence: 99%
“…However, to date, no sufficiently discriminatory multilocus genotyping scheme has been fully validated or widely adopted by veterinary or public health researchers (Hotchkiss et al., ) or reference laboratories in Europe, although an initiative as part of COST Action Euro‐FBP is addressing this issue (Chalmers and Cacciò, ). However, in most countries Cryptosporidium is not routinely genotyped, or even the infecting or contaminating species identified, and so point of reservoir source attribution is further hampered.…”
Section: Assessmentmentioning
confidence: 99%
“…They also detected high levels of recombination within the C. hominis populations, evidenced by linkage disequilibrium decay. The genetic diversity of C. hominis encountered in the Bangladesh study was found to be far greater than that seen in northern Europe, where the predominant C. hominis IbA10G2 subtype is highly conserved at the genome level (50,71). This study reveals the importance of high-throughput, wide scale genomic sequencing and analysis in elucidating the complex population structure of the parasite worldwide (31).…”
Section: Progression Of Whole Genome Sequencing and Assemblymentioning
confidence: 77%
“…For public health purposes it is desirable to have consensus to enable cross-boundary comparisons and investigations and track international spread. An initiative funded by EU COST Action FA1408 "A European Network for Foodborne Parasites: Euro-FBP" (http://www.euro-fbp.org) enabled a workshop to be held between 23 scientists and experts in public and animal health from 12 European countries and the USA on Cryptosporidium genotyping (71). The participants discussed the need for, and potential directions of, a standardized typing scheme specifically for surveillance and outbreak investigations.…”
Section: Multilocus Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…With a wide spectrum of FBPs, identifying priority research areas is difficult. Priority topics in Europe indicated by the EKE (Figure 2A) It is not always sufficient to detect an FBP in both patients and a suspected food source, and a robust, standardized, multilocus typing scheme is often needed [39]. Advances in whole-genome sequencing (WGS) of FBPs has lagged behind that of other pathogens, particularly bacteria [40], and, although ideal, the level of detail provided by WGS may be unnecessary for providing usable epidemiological evidence.…”
Section: Addressing Current Needs Within Fbps In Europementioning
confidence: 99%